Visualization and Mapping of Research Topics Transportation Model Sustainable Movement for Livestock Folding Container Ship as Sea Toll Supports - Sutini Sutini; Mudjiastuti Handajani; Ismiyati Ismiyati (Department of Urban and Regional Planning, Universitas Diponegoro, 2024)
A study analyzed research on transportation models for livestock folding containers in relation to sea toll support, utilizing Crossref data and the Publish or Perish 8 software. Searches with keywords